Pertanggungjawaban Pidana Pelaku Kekerasan Seksual Berbasis Elektronik Artificial Intelegence (Deep Fake Porn) - Putri, Nadea Aulia; Apriyani, Maria Novita (Wajah Hukum, 2025)
The problem of deep fake porn in Indonesia is not a new problem considering that many cases have occurred in the wider community and technological developments cannot be stopped. Easy access in implementing deep fakes means that anyone can create or edit any type of video or photo using the face of someone they want, of course this is done without the consent of the owner of the face so that the perpetrators are obliged to be responsible for their actions. The research applies juridical methods- Normative uses statutory, case and conceptual approaches with descriptive methods to describe legal problems that occur. The aim of this research is to determine criminal liability carried out by perpetrators of sexual violence electronically using Artificial Intelligence (AI) technology. The research results show that specific legal regulations regarding Artificial Intelligence (AI) technology do not yet exist in Indonesia, but there are laws and regulations that can be used to enforce the law. The Pornography Law and the ITE Law have elements that are more comprehensive and clear than other laws and are expected to provide fair punishment for perpetrators. The existence of criminal liability can ensure that only individuals who are responsible for their actions are punished. People who cannot be held responsible for criminal acts of pornography, namely disabled people, those who are not yet adults, carry out office orders and statutory provisions.